Perioperative Indicators of Prognosis in Acute Invasive Fungal Sinusitis. Issue 1 (March 2021) - Gardner, James Reed; Hunter, Courtney J.; Vickers, Donald; King, Deanne; Kanaan, Alissa
Objective: The purpose of this study is to identify perioperative independent prognostic factors that are available to the consulting team to aid in determining prognosis in patients with acute invasive fungal sinusitis. Study Design: Retrospective chart review of patients with biopsy-proven acute invasive fungal sinusitis from 2015 to 2018. Setting: Academic tertiary care center. Methods: Twenty-one patients were included from our single-center retrospective review. Kaplan-Meier graphs were created, and the Breslow test used to compare the curves to obtain P values. A univariate Cox regression analysis was performed on the data that were significant at 3 months from diagnosis. Results: Twenty-one patients were included, and 17 (76%) had an underlying hematologic malignancy. Overall survival was 71% and 52% at 1 and 3 months, respectively, and 94% of patients with hematologic malignancy had an absolute neutrophil count ≤1 at diagnosis. Absolute neutrophil count values and fungal species were not associated with a difference in prognosis. Factors associated with decreased survival included current smoking and the absence of a rhinologist on the treatment team at the initial or subsequent debridement (hazard ratio, 3.03). Laboratory values such as beta-D-glucan and galactomannan were assessed in addition to disease extension at diagnosis. Conclusion: This study presents a retrospective review of a single institution's experience with acute invasive fungal sinusitis. Subspecialty level of care likely improves overall survival in these patients, whereas current smoking may imply a worse prognosis.